Managerial Overconfidence, Government Intervention and Corporate Financing Decision - Irene, Wei Kiong Ting; Hooi, Hooi Lean; Qian, Long Kweh; Noor Azlinna, Azizan (Emerald Group Publishing Limited, 2016)
The purpose of this paper is to investigate the impact of managerial overconfidence on corporate financing decision and the moderating effect of government ownership on the relationship between managerial overconfidence and corporate financing decision.